Effects of even- versus uneven-aged tree species mixing on stem radial growth: Links to xylem traits and seasonal climate sensitivity - Renjie Chen; Xinyi Guan; Huizhen Nong; Angang Ming; Weijun Shen; Steven Jansen (Agricultural and Forest Meteorology, 2026)

Divergent Responses to 16 Years Near-Natural Transformation: Forest-Type Specific Regulation of Soil Microbial Communities in Subtropical Coniferous Plantations - Angang Ming; Jian Chen; Weiei Shu; Xiaoguo Zhou; Yuying Liang; Huilin Min; Guangyu Xue; Dongjing Sun; Yi Tao; Yeming You; Yingzhuo Xi; Shirong Liu (Journal of Soil Science and Plant Nutrition, 2026)

Mild Decade‐Warming Shifts Soil Organic Carbon Composition Without Altering Total Stock in Temperate and Subtropical Forests - Yujing Yang; Hui Wang; Shirong Liu; Jianming Xue; Peter Clinton; Yanchun Liu; Lin Chen; Jiatai Xiong; Jian Wang; Weijian Jiang; Qingqian Ma; Angang Ming; et al. (Ecology Letters, 2026)
Although soil respiration is known to increase with warming, the long‐term stability of total forest soil organic carbon (SOC) stocks and their compositional changes remain uncertain. Through a 12‐year soil warming experiment (+1.21°C) in temperate and subtropical forests, we found that SOC content remained stable in both 0–10 cm and 10–20 cm layers. A supporting global meta‐analysis further indicated that substantial SOC loss in forests occurs only under sustained warming exceeding 2°C. However, after 12 years, warming induced distinct compositional shifts. In the temperate forest, mineral‐associated C and the aromatic C/O‐alkyl C ratio declined, suggesting weakened mineral protection and lignin decomposition. Conversely, in the subtropical forest, alkyl C and the alkyl C/O‐alkyl C ratio increased, indicating accumulation of recalcitrant compounds. These results demonstrate that while mild long‐term warming below 2°C can maintain overall SOC stocks, it drives ecosystem‐specific compositional transformations that may influence future soil C persistence under continued climate change.

Decreased management intensity and mixed planting enhance Eucalyptus productivity through improved soil quality under eco-silviculture management in southern China - Jingwen Chen; Yongjie Huang; Xiaoguo Zhou; Yuanguang Wen; Qiuhai Chen; Hui Gao; Dongjing Sun; Lei Wang; Angang Ming; Hans Lambers (Plant and Soil, 2025)

Age-dependent tree species mixing effects on root resource acquisition strategies in Pinus massoniana plantations - Huiqing Song; Qilan Cen; Jiaqi Ya; Huizhen Qin; Peng He; Angang Ming; Shidan Zhu; Weijun Shen (Plant and Soil, 2025)

Tree species mixing promotes surface soil organic carbon accumulation in mid-age and stability in old-growth forests - Zhenkai Qin; Yanxia Nie; Angang Ming; Kun Yang; Huilin Min; Hui Wei; Weijun Shen (Plant and Soil, 2025)

Nitrogen-fixing tree species enhance the positive effects of tree species richness on soil organic carbon sequestration by increasing fine root phosphorus loss - Yanchun Liu; Qinglin Li; Huimin Tian; Shirong Liu; Chuang Ma; Menghan Wang; Hui Wang; Angang Ming (CATENA, 2025)

Soil respiration related to the molecular composition of soil organic matter in subtropical and temperate forests under soil warming - Yanchun Liu; Hui Wang; Andreas Schindlbacher; Shirong Liu; Yujing Yang; Huimin Tian; Lin Chen; Angang Ming; Jian Wang; Jiachen Li; Zuwei Tian (Soil Biology and Biochemistry, 2025)

Introducing N2-fixing tree species into Eucalyptus plantations increases organic phosphorus transformation but decreases its accumulation within aggregates in subtropical China - Haocheng Xu; Yeming You; Yi Wang; Guannv Gao; Angang Ming; Xueman Huang (Plant and Soil, 2024)

Tree species mixing effects on the radial growth of Pinus massoniana and Castanopsis hystrix: A comparison between even-aged and uneven-aged stands - Renjie Chen; Xiali Guo; Yuxian Ge; Qidong Li; Angang Ming; Huilin Min; Weijun Shen (Forest Ecology and Management, 2024)

Mixture enhances microbial network complexity of soil carbon, nitrogen and phosphorus cycling in Eucalyptus plantations - Fangcuo Qin; Fucheng Yang; Angang Ming; Hongyan Jia; Bingjiang Zhou; Junfei Xiong; Junkun Lu (Forest Ecology and Management, 2024)

Nitrogen-fixing tree species modulate species richness effects on soil aggregate-associated organic carbon fractions - Yuqian Ye; Hui Wang; Junwei Luan; Jinhao Ma; Angang Ming; Baoliang Niu; Cuiju Liu; Zac Freedman; Jingxin Wang; Shirong Liu (Forest Ecology and Management, 2023)

Introducing N2-fixing tree species into Eucalyptus plantations promotes soil organic carbon sequestration in aggregates by increasing microbial carbon use efficiency - Wen Zhang; Yeming You; Xiaoyan Su; Jinliu Yan; Guannv Gao; Angang Ming; Weijun Shen; Xueman Huang (CATENA, 2023)

Tree species mixture inhibits soil organic carbon mineralization accompanied by decreased r-selected bacteria - Xiao Zhang; Shirong Liu; Yongtao Huang; Shenglei Fu; Jingxin Wang; Angang Ming; Xiangzhen Li; Minjie Yao; Huan Li (Plant and Soil, 2018)